2019
DOI: 10.1177/0017896919826374
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Mental Health Literacy in a UK university campus population: Positive replication of a Canadian intervention

Abstract: Objectives: Mental health concerns on university campuses are increasing in the UK. Improving mental health literacy (MHL) for students may be a useful part of an integrated approach to effectively address these concerns. This study evaluated a previously demonstrated effective Canadian campus MHL resource in a UK student sample. Design: This cross-sectional study conducted on one UK campus reports on student’s opinions about the impact of the Transitions (2nd edition) resource as well as applying a standard m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…These findings are consistent with the previous research on earlier versions of the Transitions, reporting it to be a helpful resource with demonstrated benefits for student postsecondary life. [40][41][42]47 The findings described herein not only replicated those findings in short term and further at 2-month follow-up using a more robust research design on more validated outcomes across different institutions. The finding that students who had lower mental health knowledge scores at baseline improved most indicates that it may be especially beneficial to students with a poor understanding about mental health.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These findings are consistent with the previous research on earlier versions of the Transitions, reporting it to be a helpful resource with demonstrated benefits for student postsecondary life. [40][41][42]47 The findings described herein not only replicated those findings in short term and further at 2-month follow-up using a more robust research design on more validated outcomes across different institutions. The finding that students who had lower mental health knowledge scores at baseline improved most indicates that it may be especially beneficial to students with a poor understanding about mental health.…”
Section: Discussionsupporting
confidence: 76%
“…This most recent version of the Transitions updated the previous edition by including input from first-year university/college students, mental health experts, student-services staff, and faculty members. Building on previous research using earlier versions of Transitions that had demonstrated preliminary evidence on the improvements in mental health literacy, [40][41][42] this current study applied a more robust research design with control groups in a large cohort that included both university and college students in five institutions of higher learning in Canada. This study hypothesized that mental health literacy embedded in a life skills resource for first-year students in postsecondary settings would promote student's understanding about mental health, improve their attitudes toward mental illness, reduce stigma against mental illness, improve their help-seeking efficacy and general health, and reduce perceived stress.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of regressions extends previous research in this area (e.g., Gorczynski et al, 2017;O'Connor & Casey, 2015). Whilst the relationship between MHL and help-seeking is well-reported (e.g., Altweck et al, 2015;Gagnon et al, 2015;Gorczynski et al, 2017;O'Connor & Casey, 2015;Hunt et al, 2019). As others have highlighted, this study suggests that further work is needed to identify the strength of the association between MHL and psychological distress (e.g., Dumesnil & Verger, 2009;Reavley et al, 2014).…”
Section: The Relationship Between Mhl Help-seeking Behaviour and Mental Health Outcomes (Hypothesis 1)supporting
confidence: 70%
“…In addition, help-seeking behaviour is associated with a reduction in psychological distress and improved wellbeing for undergraduate students, possibly indicating a mediating relationship between MHL and these outcomes via help-seeking behaviour (Gorczynski et al, 2017;O'Connor & Casey, 2015). Furthermore, a programme of MHL in undergraduate students is reported to: (1) improve self-reported mental health knowledge; (2) reduce stigma; (3) increase help-seeking behaviour (Hunt et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…These findings resonated with our research on a similar resource Transitions , designed for first-year postsecondary students. This research indicated students’ knowledge about postsecondary life improved and they would like to talk to others (e.g., friends, roommates, classmates, and parents) as a result of reading Transitions (Hunt et al, 2019; Kutcher et al, 2015a; Potvin-Boucher et al, 2010; Wei et al, 2022). This indicated that the MHL approach with embedded life skills may have the potential to support successful student transitions to postsecondary life as it includes comprehensive and rich information relevant to youth new life experiences.…”
Section: Discussionmentioning
confidence: 90%